2018
DOI: 10.1002/gps.5024
|View full text |Cite
|
Sign up to set email alerts
|

Does social interaction influence the effect of cognitive intervention program? A randomized controlled trial using Go game

Abstract: Objectives The purpose of this study is to clarify the influence of social interaction on the effect of a cognitive intervention program using Go. Methods A single‐blind, randomized controlled trial using a classical board game “Go” was conducted. A total of 72 community‐dwelling older adults, without previous experience playing Go, were randomly assigned to three groups: (1) a face‐to‐face group (FG) in which members attended 12 Go group lessons held once a week; (2) a non‐face‐to‐face group (NFG) in which me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…However, some cognitive processes –such as flexibility or WM‐maybe need more dosage of intervention to show effects. Maybe a more focused intervention on specific cognitive processes could show better results as other studies have found 4,13 . However, a meta‐analysis 51 have considered better the usage of multidomain interventions with computerized interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some cognitive processes –such as flexibility or WM‐maybe need more dosage of intervention to show effects. Maybe a more focused intervention on specific cognitive processes could show better results as other studies have found 4,13 . However, a meta‐analysis 51 have considered better the usage of multidomain interventions with computerized interventions.…”
Section: Discussionmentioning
confidence: 99%
“…After the first assessment, 35 older adults were randomly allocated into the GTG who played board and card games (GTG; n = 17; mean age = 80.76 ± 9.80; % women = 70.6) and into the Active Control Group who did paper‐and‐pencil cognitive tasks (ACG; n = 18; mean age = 80.89 ± 9.54; % women = 83.3). The sample was simple randomized with an allocation ratio 1:1 using random excel formula by the last author, following previous studies 13 . Both intervention groups had the same number of people from each center (See Table 2).…”
Section: Main Studymentioning
confidence: 99%
“…An intervention study focusing on social interactions showed improvements in verbal memory and working memory due to the acquisition of new intellectual skills that accompany social interaction ( 36 ). In a study that examined the effects of social interaction among cognitive interventions, intervention via acquisition of new intellectual skills through analog games was found to affect visual working memory, and the effect increased with social interaction ( 37 ). It is also possible that intake of Amino LP7 first improved psychological health, which in turn led to improved social interaction and attention and executive function.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the effects of social participation, it is necessary to develop appropriate interventions for older adults and provide them with more opportunities for cognitive stimulation through various social activities. Several studies have examined the effect of exercise or cognitive activities on social interaction on cognitive function (Iizuka et al, 2019; Rektorova et al, 2019). However, isolating social factors for analysis was not feasible; therefore, social engagement includes physical and cognitive aspects in addition to social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of social activity, for example, folk dancing and playing card games, include physical, social, and cognitive elements that stimulate the cognitive process. A study evaluating the impact of board games on cognitive function found that the effect size of the group playing games with other people was greater than that of the group playing games alone using tablets (Iizuka et al, 2019). According to Piccirilli and colleagues (2019), a positive effect on cognitive function could be anticipated through integrative activities that incorporate physical, mental, and social elements.…”
Section: Discussionmentioning
confidence: 99%